2014
DOI: 10.1038/ki.2013.517
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic modeling of enterohepatic circulation of mycophenolic acid in renal transplant recipients

Abstract: Several factors contribute to mycophenolic acid (MPA) between-patient variability. Here we characterize the metabolic pathways of MPA and quantify the effect of combining genetic polymorphism of multidrug-resistant-associated protein-2, demographics, biochemical covariates, co-medication (cyclosporine (CsA) vs. macrolides), and renal function on MPA, 7-O-MPA-glucuronide (MPAG), and acyl-glucuronide (AcMPAG) disposition, in renal transplant recipients, after mycophenolate mofetil. Complete pharmacokinetic profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 45 publications
(91 reference statements)
5
37
0
Order By: Relevance
“…Table 3, the population estimate of CL uMPA /F (852 L/h) was comparable to most of previously reported values in Caucasians (654-866 L/h) [27][28][29]. Moreover, the calculated typical value of apparent clearance of tMPA (CL tMPA /F, 15.68 L/h) was also comparable to most of previously reported values (12.3-20.8 L/h) [17][18][19][20][21][22][23][24][25][26]. The population estimate of FU MPA in our study (1.84%) was similar to values reported by van Hest et al [28] and Colom et al [29] (2.03% and 1.93%, respectively).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Table 3, the population estimate of CL uMPA /F (852 L/h) was comparable to most of previously reported values in Caucasians (654-866 L/h) [27][28][29]. Moreover, the calculated typical value of apparent clearance of tMPA (CL tMPA /F, 15.68 L/h) was also comparable to most of previously reported values (12.3-20.8 L/h) [17][18][19][20][21][22][23][24][25][26]. The population estimate of FU MPA in our study (1.84%) was similar to values reported by van Hest et al [28] and Colom et al [29] (2.03% and 1.93%, respectively).…”
Section: Discussionsupporting
confidence: 88%
“…population pharmacokinetics, unbound mycophenolic acid, linear protein binding, adult kidney transplant recipients tMPA population PK [17][18][19][20][21][22][23][24][25][26]. There are few investigations of the population PK characteristics of unbound MPA (uMPA) [27][28][29][30], the pharmacologically active component, due to the technical complexity of measurements.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Other data showed that renal function, serum albumin concentrations, hemoglobin levels and immunosuppressive co-medication, such as TAC, are factors contributing to the variability and time-dependent pharmacokinetics of drug treatments. 22,23 In this study, in which we aimed to translate in vitro the doses of ISDs used in clinical protocols, we tested a range of concentrations (TAC: 0.08-20 ng/mL; MPA: 0.08-2.5 µg/mL; mPr: 0.015-4 mg/mL) including both maximum and minimum therapeutic levels of ISDs, described in transplanted patients. [24][25][26] The doses leading to 50% of Treg viability (LD50) (2 ng/mL, 1 mg/mL and 0.5 mg/mL for TAC, MPA and mPr, respectively) were selected and used for the in vitro analysis ( Figure 1A-C).…”
Section: Treg Viability Is Affected By the Presence Of Immunosuppressmentioning
confidence: 99%
“…In our study, at day 7 post-transplantation, mean MPA CL increased from 7.80 to 54.30 L/h for tacrolimus-cotreated patients. This may be caused by a combination of improving renal function during the first weeks post-transplantation 25 .…”
Section: Discussionmentioning
confidence: 99%